2020
DOI: 10.1063/5.0003103
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the electric-dipole approximation in simulations of x-ray absorption spectroscopy: Lessons from relativistic theory

Abstract: We present three schemes to go beyond the electric-dipole approximation in x-ray absorption spectroscopy calculations within a fourcomponent relativistic framework. The first is based on the full semi-classical light-matter interaction operator and the two others on a truncated interaction within the Coulomb gauge (velocity representation) and multipolar gauge (length representation). We generalize the derivation of the multipolar gauge to an arbitrary expansion point and show that the potentials corresponding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 104 publications
(150 reference statements)
0
44
0
Order By: Relevance
“…The right-hand side of eq 4 describes the interaction of the molecular system with the applied external electric field, which in the electric dipole approximation is mediated by the electric dipole moment operator P . While the short wavelength of X-ray radiation may require terms beyond the electric dipole, 81 83 we do not consider this aspect in the present study. Finally, the first term on the left-hand side of eq 4 is the generalized Hessian; for the Dirac–Coulomb Hamiltonian, it is defined by 63 where ε i and ε a are the energies of occupied and virtual reference MOs, respectively, δ pq is the Kronecker delta function (δ pq = 1 if p = q and 0 otherwise), and is the coupling matrix, with ξ denoting the admixture of HFX.…”
Section: Theorymentioning
confidence: 99%
“…The right-hand side of eq 4 describes the interaction of the molecular system with the applied external electric field, which in the electric dipole approximation is mediated by the electric dipole moment operator P . While the short wavelength of X-ray radiation may require terms beyond the electric dipole, 81 83 we do not consider this aspect in the present study. Finally, the first term on the left-hand side of eq 4 is the generalized Hessian; for the Dirac–Coulomb Hamiltonian, it is defined by 63 where ε i and ε a are the energies of occupied and virtual reference MOs, respectively, δ pq is the Kronecker delta function (δ pq = 1 if p = q and 0 otherwise), and is the coupling matrix, with ξ denoting the admixture of HFX.…”
Section: Theorymentioning
confidence: 99%
“…However, in contrast to the generalized velocity representation, we now loose origin independence of oscillator strengths. 28 In our previous work, 28 however, we have have shown that it is possible within the generalized velocity representation to distinguish electric and magnetic multipole components, while maintaining origin independence of the oscillator strengths, although its individual components still exhibit this dependency. The operator manipulations required for this separation do not involve commutators with the Hamiltonian and are therefore also valid when using finite basis sets.…”
Section: Multipoles In the Velocity Representationmentioning
confidence: 91%
“…The use of Fermi's golden rule for a transition between discrete states is justified by the inclusion of a (Lorentzian) lineshape function f (ω, ω f i , γ f i ) expressing the finite lifetime of excited states (see discussion in Ref. 28). Moreover, the lineshape function, having the dimension of time, has to be included in order for the absorption cross section to have the correct dimension of area.…”
Section: Full Light-matter Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…138 Transition moments may be calculated with user-specified property operators. From DIRAC20 onward, three schemes 139 to go beyond the electric dipole approximation in the calculation of oscillator strengths will be available in DIRAC. The first is based on the full semi-classical lightmatter interaction operator and the two others on a truncated interaction within the Coulomb gauge (velocity representation) and multipolar gauge (length representation).…”
Section: Scf Calculationsmentioning
confidence: 99%